ADMINISTRATIVE PRACTICES OF THE KHWARAZM EMPIRE: LESSONS FOR MODERN GOVERNANCE - Kalandarov Bilolkhon Jalolkhon ugli (Journals Park Publishing, 2024)
The administrative system of the Khwarazm Empire, which thrived between the 11th and 13th centuries, offers valuable insights into governance that can be adapted for modern administration. This article explores the administrative practices of the Khwarazm Empire, focusing on its centralized bureaucracy, regional governance, tax system, and its innovative approach to public order and legal administration. By analyzing these practices, this paper seeks to identify key lessons for contemporary governance, particularly in terms of state-building, resource management, and conflict resolution.
Keywords: Khwarazm Empire, administrative system, governance, bureaucracy, taxation, regional governance, legal administration, public order, state-building.